Preclinical Toxicological Characterization of Porphyrin-Doped Conjugated Polymer Nanoparticles for Photodynamic Therapy - Matías Daniel Caverzan; Ana Belén Morales Vasconsuelo; Laura Cerchia; Rodrigo Emiliano Palacios; Carlos Alberto Chesta; Luis Exequiel Ibarra (Pharmaceutics)
Background: Photodynamic therapy (PDT) utilizing nano-based photosensitizers (PSs) offers promising cancer treatment potential but requires rigorous safety evaluation. Conjugated polymer nanoparticles (CPNs) doped with porphyrins, such as platinum porphyrin–doped poly(9,9-dioctylfluorene-alt-benzothiadiazole) (F8BT), exhibit enhanced photodynamic efficiency but lack comprehensive preclinical toxicity data. This study aimed to evaluate the biocompatibility, biodistribution, and acute/subacute toxicity of these CPNs to establish their safety profile for clinical translation. Methods: CPNs were synthesized via nanoprecipitation using amphiphilic stabilizers (PSMA or PS-PEG-COOH) and characterized for colloidal stability in parenteral solutions. Hemolysis assays were used to assess blood compatibility. Single-dose (0.3 and 1 mg/kg, intravenous) and repeated-dose (0.1–1 mg/kg, intraperitoneal, every 48 h for 28 days) toxicity studies were conducted in BALB/c mice. Hematological, biochemical, histopathological, and biodistribution analyses (via ICP-MS) were performed to evaluate systemic and organ-specific effects. Results: CPNs demonstrated excellent colloidal stability in 5% dextrose, with minimal aggregation. No hemolytic activity was observed at concentrations up to 50 mg/L. Single and repeated administrations revealed no significant changes in body/organ weights, hematological parameters (except transient fibrinogen elevation), or liver/kidney function markers (ALT, AST, BUN, Cr). Histopathology showed preserved tissue architecture in major organs, with mild hepatocyte vacuolation at 30 days. Biodistribution indicated hepatic/splenic accumulation and rapid blood clearance, suggesting hepatobiliary elimination. Conclusions: Platinum porphyrin–doped F8BT CPNs exhibited minimal acute and subacute toxicity, favorable biocompatibility, and no systemic adverse effects in murine models. These findings support their potential as safe PS candidates for PDT. However, chronic toxicity studies are warranted to address long-term organ accumulation and metabolic impacts. This preclinical evaluation provides a critical foundation for advancing CPNs toward clinical applications in oncology.